Analisis Pengakuan Pendapatan dan Beban Menurut PSAK No. 28 Pada PT. Asuransi Bangun Askrida Tahun 2019-2021 - Novalia, Salma; Syahrif, Rafi; Uzliawati, Lia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
PT Asuransi Bangun Askrida (ASKRIDA) is a national private insurance company that provides protection against various risks and losses, especially for government buildings and other assets owned by the government. The purpose of this study is to obtain empirical data regarding the recognition of insurance loss expenses at PT Asuransi Bangun Askrida (ASKRIDA) and to evaluate whether the recognition and presentation of the company's expenses are in accordance with the provisions of PSAK No. 28. The research methodology uses descriptive qualitative where information is collected, assembled, interpreted, and evaluated to offer comprehensive insights to address the problem. Based on the research results, PT Asuransi Bangun Askrida (ASKRIDA) takes a different approach in terms of revenue and expense recognition based on PSAK No. 28. In claim expense recognition, PT Asuransi Bangun Askrida (ASKRIDA) recognizes claim expenses when incurred without regard to the status of the reported claim. This indicates the need for adjustments in revenue recognition practices to comply with applicable accounting standards.